Nurse Managers’ Perception and Practice on the Theory of Technological Competency as Caring in Nursing: A Preliminary Study - Nakano, Yoko; Yokotani, Tomoya; Takashima, Yoshiyuki; Betriana, Feni; Osaka, Kyoko; Kataoka, Mutsuko; Tanioka, Tetsuya; Locsin, Rozzano C (Jurnal Keperawatan Soedirman, 2023)
In spite of emphasis on patient-centered care and promotion of their quality, shortcomings have been seen in psychiatric care due to lack of compassion. To improve the quality of psychiatric caring in nursing, it is important to develop and implement in-service education based on Locsin’s Technological Competency as Caring in Nursing (TCCN) theory. Objectives to determine psychiatric nurse managers' perception and practice status as a preliminary survey to serve as a resource for in-service psychiatric nursing education. This survey was conducted in August 2022 using the Technological Competency as Caring in Nursing Instrument-Revised for Practice (TCCNI-Repract) scale at "A" psychiatric hospital. Descriptive statistics and Wilcoxon's signed-rank tests were used. Eleven head nurses and assistant head nurses participated in this study. Mean values for the perception dimension of each item of the TCCNI-RePract were high, whereas mean values for practice dimension were low. The results indicated that perception dimension was significantly higher than practice dimension in 21 of 26 items of the TCCNI-RePract. Nurse managers demonstrated a high level of perception of the TCCN theory; however, many practical items scored low. Nurse managers suggested developing a current educational program to inform practice based on the TCCN theory.